L. da Vinci's Turbulence, Multi-dimensional Golden Spinors, Prandtl's Boundary Layer and Quantum Mechanical Spin are all implied by the Golden Number System - Elnaschie, M. S. (European Journal of Applied Sciences, 2021)
The present short paper proposes a new elucidation of quantum spin as a higher dimensional golden spiral akin to da Vinci’s fluid turbulence and various related nonlinear dynamic subjects. In particular and as an extension of the Fibonacci spinor all the obtained conclusions are almost a trivial consequence of taking the limit of iterating the said Fibonacci spinor and are thus implied as part and parcel by the use of the E-Infinity golden mean number system developed in the Greek-Egyptian Alexandria school of science by the dedicated work of Plato, Pythagoras, their followers and disciples.